Den/dem anderen Raum geben: feministisch-christliche Identität ohne Antijudaismus - Wacker, Marie-Theres (Von der Wurzel getragen, 1996)
This contribution first sketches the particular dilemma of identity experienced by Christian feminist theologians in dealing with anti-Judaism. In a second section the contributions to the present volume, and the significance of their results in relation to this discussion are systematically evaluated. The third section aims to draw attention to problems confronting a Christian feminist exegesis which is concerned with access to the Bible as a whole, thus dealing in particular with the question of the classification of "Old" and "New" Testament.